URGENSI KEPALA SEKOLAH SEBAGAI PEMIMPIN PEMBELAJARAN DALAM MENCAPAI SEKOLAH BERPRESTASI PADA ERA DIGITAL - sulistyorini, Sulisytorini (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2023)
This study aims to find out about the urgency of school principal leadership in achieving outstanding schools in the digital era. This study uses a qualitative approach, by seeking to explore the forms, factors, and implications of principal learning leadership in the digital era. Data collection was conducted using participant observation at MTsN 2 Blitar and interviews with the principal and five teachers at the school. The results of this study indicate that, first, the principal’s learning leadership in the digital era is by creating a school environment that is responsive to digitalization, providing LEDs in each class and allowing students to bring smartphone to school according to the needs and material presented by the teacher. Second, there are challenging factors that come from within and from outside the institution, including human resources that do not respond to digital learning and external obstacles, the lack of funds from the Ministry of Religion for digitalization-based learning, and the lack of supporting infrastructure for digital learning in madrasas. The three implications of the school principal’s learning leadership are the creation of a conducive digital- based learning environment climate so that institutional and student achievements, both academic and non-academic, are achieved so that they become national-level pilot madrasah.